Effectiveness of Mobile Applications in Arabic Language Learning for Elementary School Students - Ramadani, Putra; Hasan, Laili Mas Ulliyah (Universitas Al-Amien Prenduan, 2024)
This research explores the role of mobile technology in Arabic language education at the elementary school level. With the increasing use of technology in education, this research highlights how mobile applications can be used as effective learning tools. The purpose of this research is to measure the effectiveness of using mobile applications in Arabic language learning for elementary school students. This research employs a mixed-methods approach that combines quantitative and qualitative methods. Quantitative data was obtained through Arabic language proficiency tests conducted before and after the use of the application, while qualitative data was collected through interviews with students and teachers to gain in-depth insights into their experiences. The results of the study indicate that the use of the mobile application significantly improved students' Arabic language skills, particularly in the areas of vocabulary, reading, and grammar. In addition, this research also reveals that the majority of students and teachers have a positive perception of the use of mobile applications in learning, although there are challenges such as limited access to technology and the need for adequate technical support and training. The recommendations provided include the enhancement of technological infrastructure, support and technical training, collaboration between application developers and educators, as well as parental involvement. This research provides valuable insights into the potential and challenges of using mobile technology in Arabic language education, as well as laying the groundwork for better development and implementation in the future.